Defect formation dynamics in dry and water submerged graphene nanosheets. (24th April 2019) - Sharma, Saurabh S; Sharma, Bharat Bhushan; Parashar, Avinash
Abstract: In this article, molecular dynamics-based simulations were performed to study the defect formation dynamics in dry and wet form of graphene nanosheets. Atomistic simulations were performed with the help of hybrid interatomic potentials that includes reactive force field for graphene, TIP3P for water and non-bonded Lenard Jones for interface between water and graphene. It was predicted from the simulations that graphene nanosheets are more stable, while submerged in water. Graphene sheet containing vacancy defects were predicted to be more stable, whereas more resistance was offered by graphene in water to dislodge atoms from its lattice position. It can be concluded from the simulations that non-bonded interactions experienced by graphene nanosheet in water helps in maintaining a higher structural stability as compared to graphene in dry state. These studies will help in developing applications for graphene in marine as well as space structures, where material is more susceptible to ion bombardment and defect generation.